Planning for death: wills and death-related property arrangements in Europe, 1200-1600 - Korpiola, Mia; Lahtinen, Anu (Medieval law and its practice)
Introduction / Mia Korpiola and Anu Lahtinen -- Inheritance law, wills, and strategies of heirship in medieval Sweden / Mia Korpiola and Elsa Trolle Onnerfors -- Monastic donations by widows : morning gifts as assets in planning for old age and death in fifteenth-century Sweden / Tuula Rantala -- Competing interests in death-related stipulations in South Tirol, c. 1350-1600 / Christian Hagen, Margareth Lanzinger, and Janine Maegraith -- Medieval English lawyers' wills and property strategies / Anthony Musson -- Men and women preparing for death in renaissance Venice (c. 1200-1600) / Federica Mase -- Mutual testaments in late medieval Stockholm, c. 1420-1520 / Marko Lamberg -- Wills as tools of power: development of testamentary practice in krakow during the late middle ages / Jakub Wysmulek -- Deathbed strife and the law of wills in medieval and early modern England / R.H. Helmholz -- The will of Filippa Fleming (1578), family relations, and Swedish inheritance law / Anu Lahtinen